2018
DOI: 10.1002/humu.23411
|View full text |Cite
|
Sign up to set email alerts
|

The BRCA2 c.68-7T > A variant is not pathogenic: A model for clinical calibration of spliceogenicity

Abstract: Although the spliceogenic nature of the BRCA2 c.68‐7T > A variant has been demonstrated, its association with cancer risk remains controversial. In this study, we accurately quantified by real‐time PCR and digital PCR (dPCR), the BRCA2 isoforms retaining or missing exon 3. In addition, the combined odds ratio for causality of the variant was estimated using genetic and clinical data, and its associated cancer risk was estimated by case‐control analysis in 83,636 individuals. Co‐occurrence in trans with pathoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 36 publications
5
24
0
Order By: Relevance
“…Moreover, the reproducibility of MGBR2_2–9 splicing outcomes was supported by previous studies based on patient RNA or minigene data, according to which fourteen variants matched preceding results: c.67+3A>G, c.68‐7T>A, c.316+3del, c.316+5G>C, c.426‐12_426‐8del, c.467A>G, c.516+ 1G>T, c.517G>T, c.572A>G, c.617C>G, c.627C>A/T, c.631G>A, c.631+3A>G and c.681+4A>G . Conversely, in a recent publication, variant c.68‐7T>A induced 20% of transcript Δ3 in lymphoblastoid cell lines of carrier patients versus 2.8% of Δ3 and 7.2% of Δ(6q 39 ,7) found in our minigene study in MCF‐7 cells . These variations may be due to technical differences in RNA isolation methods, retro‐transcriptases, DNA polymerases, primers and product length, thermocycling protocol as well as cell‐type specific variations between the patient sample and the minigene assay.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the reproducibility of MGBR2_2–9 splicing outcomes was supported by previous studies based on patient RNA or minigene data, according to which fourteen variants matched preceding results: c.67+3A>G, c.68‐7T>A, c.316+3del, c.316+5G>C, c.426‐12_426‐8del, c.467A>G, c.516+ 1G>T, c.517G>T, c.572A>G, c.617C>G, c.627C>A/T, c.631G>A, c.631+3A>G and c.681+4A>G . Conversely, in a recent publication, variant c.68‐7T>A induced 20% of transcript Δ3 in lymphoblastoid cell lines of carrier patients versus 2.8% of Δ3 and 7.2% of Δ(6q 39 ,7) found in our minigene study in MCF‐7 cells . These variations may be due to technical differences in RNA isolation methods, retro‐transcriptases, DNA polymerases, primers and product length, thermocycling protocol as well as cell‐type specific variations between the patient sample and the minigene assay.…”
Section: Discussionmentioning
confidence: 99%
“…Authors found that although BRCA1 c.(594–2A>C; 641A>G) alleles did not contribute to full‐length transcript expression and produced a major frameshift event lacking exon 10, an estimated proportion of 30% of Δ9,10 isoform was sufficient to confer tumor suppressor capacity in variant carriers (la Hoya et al, ). Another example illustrating the complexity of splicing interpretation is BRCA2 c.68–7T>A variant, for which authors concluded that BRCA2 alleles producing up to approximately 20% exon 3 skipping were not associated with cancer risk (Colombo et al, ). Here, we describe three variants producing “leaky” splicing effects (see BRCA1 c.135–18 T>G, BRCA2 c.9501+3A>T and BRCA2 c.7447A>G variants in Figures a, and e,f, respectively), and the methodology used in this study is limited for the clinical interpretation of this type of variants.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported that variants affecting splicing, namely spliceogenic, are the third most common type occurring in BRCA1 and BRCA2 genes, accounting for 10.1% and 7.6% of the total, respectively (Rebbeck et al, ). Although multiple spliceogenic variants producing abnormal transcripts have been identified in HBOC families, the clinical relevance of the splicing outcomes can be sometimes difficult to determine (de Caputo et al, ; Colombo et al, ; la Hoya et al, ; Montalban et al, ). Furthermore, numerous BRCA1/2 alternative splicing events have been described in several tissues and cell lines, adding complexity to the interpretation of splicing outcomes generated from variant alleles (Colombo et al, ; Fackenthal et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…These assays are accessible to most laboratories, can be performed in patient samples, do not require the use of expression vectors, and can perform qualitative characterization of splicing variants; however, these assays only provide semi-quantitative data and lack the throughput required to analyze a large amount of variants ( 30 , 31 ). Alternatively, there are quantitative approaches, including real-time and digital PCR, that provide robust and reliable quantitative data ( 29 , 32 ), but cannot perform qualitative analysis (i.e., these assays are unable to reveal the precise transcript sequence). Here we describe a novel RNA MPS method, CloneSeq, and demonstrated that this technique is capable of performing reliable high-throughput quantitative and qualitative analysis of splicing variants, a necessary feature to obtain evidence for the large number of alterations predicted to affect splicing in HBOC genes.…”
Section: Discussionmentioning
confidence: 99%